Beyond Calculus: Apple-apple-apple-ike and Other Embodied Pleasures for a Child Diagnosed with Autism in a Sensory Integration Based Clinic - Melissa Park (Disability Studies Quarterly, 2009)
Models of disability shift attention to how institutionalized forms of misrecognition are as debilitating as disease processes or diagnostic categories. Drawing from an ethnography of clinical practice, this article focuses on the poetic process—visible in fleeting, bodily-sensing images, gestures or nonsensical utterances like “apple-apple-ike”—that structures the interactions between a child diagnosed with autism and an occupational therapist. Microanalysis of moments of bodily attunement reveal how the emergence of embodied pleasures leads to a mutual healing of regard; that is, how techniques of bodily-sensing interventions work equally to restore the health of social relatedness. The tight entanglement between intercorporeality and intersubjectivity—embodied pleasure and recognition of the Other—foregrounds that the healing of regard must be mutual. Reframing rehabilitation research in terms of aesthetics and folk neurology considers what is at stake in developing a language to grasp what constitutes evidence of healing beyond a calculus of discrete, measureable outcomes. [Keywords: aesthetics, clinical reasoning, intersubjectivity, occupational therapy, recognition]
Keywords: aesthetics; clinical reasoning; intersubjectivity; occupational therapy; recognition